A comparative evaluation of the three prominent approaches in adaptable software architecture - Maznan, Roslinda; Wan Kadir, Wan Mohd. Nasir (2006)
Due to the inherent dynamic nature of the software environment, software evolution is inevitable. A large portion of total software lifecycle cost is devoted to introducing new requirements, and removing or changing the existing requirements. Many research projects attempt to find a more applicable way for building a software system that is flexible to changes. These efforts lead to the extensive study in software architecture that is adaptable to changes. In this paper, we compare three prominent approaches to adaptable software architectures namely Adaptive Object Model, Coordination Contract and Aspect Oriented Programming. It provides a brief description on the properties of each approach, and explains the comparative evaluation framework that is used in the evaluation process. Sejahtera System, which has a dynamically changing user requirement, is chosen as the case study to facilitate the consistent comparison of the selected approaches. We strongly believe that the results presented in this paper may provide a foundation in improving the state-of-the-art adaptable software architecture approaches.